2003
DOI: 10.1128/aem.69.1.668-672.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella enterica Serovar Enteritidis by Ultrasonic Waves under Pressure at Different Water Activities

Abstract: The inactivation of Salmonella enterica serovar Enteritidis by ultrasonic waves (20 kHz; 117-m wavelength) under pressure (175 kPa) at nonlethal temperatures (manosonication [MS]) and lethal temperatures (manothermosonication [MTS]) in media of different water activities has been investigated. Heat decimal reduction time values increased 30 times when the water activity was decreased from nearly 1 to 0.96, but the MS resistance was increased only twofold. The inactivation of Salmonella serovar Enteritidis by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For Salmonella, pH and water activity of the treatment medium are the most influential factors (1,29). Our results demonstrated that acidification from pH 7.0 to 3.0 did not influence the UV resistance of Salmonella Typhimurium STCC 878 (Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…For Salmonella, pH and water activity of the treatment medium are the most influential factors (1,29). Our results demonstrated that acidification from pH 7.0 to 3.0 did not influence the UV resistance of Salmonella Typhimurium STCC 878 (Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…All the survival curves to MS/MTS obtained were linear, as already described, for this species when exposed to MS (Arroyo, Cebrián, Pagán, & Condón, 2011b), to MTS in buffer and milk (Arroyo et al, 2011a), and for the survival curves to MTS of other species (Álvarez et al, 2003;López-Malo, Guerrero, & Alzamora, 1999;Pagán, Mañas, Raso et al, 1999). This linear shape in MTS survival curves was also found when C. sakazakii was treated at temperatures at which survival curves to heat showed shoulders.…”
Section: Discussionmentioning
confidence: 67%
“…Among them, probably the most promising ones are the combination of ultrasound with pressure (referred to as manosonication, MS), with temperature (thermosonication) or with both simultaneously (manothermosonication, MTS) (Chemat, Huma, & Khan, 2011;Condón, Raso, & Pagán, 2005;Sala, Burgos, Condón, López, & Raso, 1995). The combination of ultrasound and heat to achieve a high degree of bacterial inactivation was first reported by Ordóñez, Aguilera, García, and Sanz (1987) and since then, it has been studied by several authors (Adekunte et al, 2010;Álvarez, Mañas, Sala, & Condón, 2003;Baumann, Martin, & Feng, 2005;Ciccolini, Taillandier, Wilhem, Delmas, & Strehaiano, 1997;D'Amico, Silk, Wu, & Guo, 2006;Guerrero, López-Malo, & Alzamora, 2001;Lee, Zhou, Liang, Feng, & Martin, 2009;Pagán, Mañas, Palop, & Sala, 1999;Pagán, Mañas, Raso, & Condón, 1999;Raso, Pagán, Condón, & Sala, 1998;Raso, Palop, Pagán, & Condón, 1998;Zenker, Heinz, & Knorr, 2003). In these works, researchers demonstrated that when ultrasound was employed, both at lethal and sublethal temperatures, an increase in the inactivation rate occurred; and some of them reported an effect much greater than the additive effect of the two treatments considered independently.…”
Section: Introductionmentioning
confidence: 98%
“…Microbial inactivation by ultrasound is mainly attributed to cavitation, a phenomenon that disrupts cellular structures and functions (13). Ultrasound alone may not effectively inactivate bacteria on food (14); however, combined with other treatments, ultrasound may result in higher bacterial lethality (15,16). It has also been reported that ultrasound is more efficient in a saline solution or in water (14).…”
Section: Introductionmentioning
confidence: 96%